(untitled) (World Economics and Finance Bulletin, 2023)
Corporate governance has received prominent attention from international and regional organizations, especially after the repeated financial crises that led to a crisis of confidence in accounting information. Hence, there was an urgent need to conduct research aimed at demonstrating the impact of corporate governance on the level and quality of disclosure and transparency in financial reports for a sample of companies. Iraqi law, as there is no legal text or legislation in Iraq specific to the mechanisms or principles of corporate governance, except for some texts that exist within the laws such as the companies law, the banking law, or other laws regulating the work of these companies. In addition, these Iraqi legislation and laws do not compensate for the absence of principles. Governance, because these principles are issued by a specialized international organization and have important paragraphs that are more precise for all stakeholders, and these paragraphs are not all present within Iraqi laws, and to achieve that goal, four mechanisms were chosen for corporate governance, which were (the administrative ownership mechanism, the ownership concentration mechanism, and the mechanism for the existence of a committee The review and the mechanism of the existence of the remuneration determination committee) for the purpose of measuring it and identifying the level of its application in those companies. As for the level of disclosure, it was measured through the Standard and Poor’s index, which is an indicator designed for that. With regard to measuring the impact of these mechanisms on the level of accounting disclosure, their impact was measured from Through the use of statistical models, the research was conducted on a sample of companies listed on the Iraqi Stock Exchange, represented by nineteen companies divided into seven economic sectors for the period from 2015 to 2019.